Magnetic Driving of AGN Jets - Vlahakis, Nektarios (AIP, 2006)
Jets in active galactic nuclei are collimated, relativistic flows that emanate from accretion disks around supermassive black holes. Electromagnetic stresses are the most plausible candidate for extracting energy at the source and converting it into outflow kinetic energy. Questions that need to be answered in order for these processes to be well understood are: Can we explain parsec-scale accelerations that the observations infer? How the conditions near the disk are related to the terminal Lorentz factor of the jet and what is the asymptotic value of the Poynting-to-matter energy flux ratio? Can we model the apparent kinematics of the observed jet components? I present solutions of the ideal magnetohydrodynamic equations that help to shed light on these questions.
Keywords: 95.30.Qd; 98.54.Cm; Active and peculiar galaxies and related systems; Magnetohydrodynamics and plasmas